Ciliated Hepatic Foregut Cyst: Definitive Diagnosis Is Critical to the Optimal Treatment Pathway - Tatsuhiro Kato; Christine M. G. Schammel; Hubert Fenton; Steven D. Trocha; A. Michael Devane (Case Reports in Hepatology)
Background. Ciliated hepatic foregut cyst (CHFC) is a rare, benign cyst of the liver, derived from the embryonic foregut epithelium. Although CHFCs are typically asymptomatic, some present with nonspecific abdominal symptoms. Imaging modalities alone are insufficient for diagnosis, with intrahepatic cholangiocarcinoma included in the differential due to nonspecific imaging features; definitive diagnosis relies on histologic confirmation. These lesions are often benign; however, larger lesions can have malignant transformation into squamous cell carcinoma (SCC), which carries a poor prognosis, thus making a definitive diagnosis, no matter what size, essential. Here, we present a case of CHFC as well as a comprehensive literature review. Given these data, we propose an algorithm for definitive diagnosis.